The Influence of Marketing Mix on Repurchase Intention for Azarine Sunscreen Product in Denpasar City - Arini Maharani Zahra; Putu Saroyini Piartrini (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The beauty industry in Indonesia has experienced rapid development in recent years with significant growth in the cosmetics sector. One of the important products in skin care is sunscreen, which protects the skin from harmful ultraviolet rays. Azarine, a local Indonesian brand, has succeeded in establishing its position in the market. This research aims to analyze the influence of the marketing mix on repurchase intention for Azarine sunscreen products in Denpasar City. This research uses quantitative methods with a survey approach to users of Azarine sunscreen products in Denpasar City. Data was collected through questionnaires distributed to 140 respondents. Data analysis was carried out using the multiple linear regression method to test the influence of product quality, price suitability, distribution channels and promotional effectiveness on repurchase intention. The results of the research show that product quality on repurchase intention obtained a significance value of 0.000, which shows that product quality has a positive and significant effect on repurchase intention. Price suitability for repurchase intention obtained a significance value of 0.000, which means price suitability has a positive and significant effect on repurchase intention. The distribution channel on repurchase intention obtained a significance value of 0.009, which means that the distribution channel has a positive and significant effect on repurchase intention. The effectiveness of promotions on repurchase intention obtained a significance value of 0.000, which means that promotion effectiveness has a positive and significant effect on repurchase intention. The research results show that the variables of product quality, price suitability, distribution channels, and promotional effectiveness have a positive and significant influence on the intention to repurchase Azarine sunscreen products. It is hoped that these findings can contribute to Azarine's management in formulating more effective marketing strategies to increase customer loyalty. This research also provides empirical contributions to academic literature in the field of marketing.